1992
DOI: 10.1073/pnas.89.18.8497
|View full text |Cite
|
Sign up to set email alerts
|

UV exposure reduces immunization rates and promotes tolerance to epicutaneous antigens in humans: relationship to dose, CD1a-DR+ epidermal macrophage induction, and Langerhans cell depletion.

Abstract: Increasing UVB radiation at the earth's surface might have adverse effects on in vivo immunologic responses in humans. We prospectively randomized subjects to test whether epicutaneous immunization is altered by prior administration of biologically equalized doses of UV radiation. Multiple doses of antigens on upper inner arm skin (UV protected) were used to elicit contact sensitivity responses, which were quantitated by measuring increases in skin thickness. If a dose of UVB sufficient to induce redness (eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
218
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(231 citation statements)
references
References 38 publications
13
218
0
Order By: Relevance
“…The UVB doses required to achieve suppression of IFN-␥-induced keratinocyte ICAM-1 up-regulation in human skin were essentially identical to those that previously were found to suppress T cell-mediated immune responses against contact allergens in human skin (24). In those experiments, UVB radiation-induced reduction of immunization rates in human skin was found to be MED-dependent, and significant immunomodulatory effects could be observed at levels of in vivo UVB exposure that were equivalent a b c Fig.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The UVB doses required to achieve suppression of IFN-␥-induced keratinocyte ICAM-1 up-regulation in human skin were essentially identical to those that previously were found to suppress T cell-mediated immune responses against contact allergens in human skin (24). In those experiments, UVB radiation-induced reduction of immunization rates in human skin was found to be MED-dependent, and significant immunomodulatory effects could be observed at levels of in vivo UVB exposure that were equivalent a b c Fig.…”
Section: Discussionsupporting
confidence: 50%
“…This would also imply that there is no linear correlation between the number of dimers and the development of immunosuppression. In support of this view, UVB radiation-induced suppression of immune responses in human skin was shown to be a function of biologically rather than physically equalized UVB radiation doses (24). Moreover, recent evidence demonstrates that keratinocyte apoptosis induced by UV (sunburn cells) is mediated by DNA damage and can be prevented even if not all cyclobutane pyrimidine dimers in DNA are repaired (32).…”
Section: Discussionmentioning
confidence: 64%
“…We argued that our original hypothesis that sun exposure increases risk of NHL was supported biologically by evidence that sun exposure causes T-cell immune suppression 11 and that risk of NHL is greatly increased in people with T cell immune deficiency associated with HIV infection or immunosuppressive therapy after organ transplantation. 12,13 Is it possible, contrary to this argument, that the effects of sun exposure on immune responses might decrease rather than increase risk of NHL?…”
Section: Resultsmentioning
confidence: 99%
“…The known capacity of UV radiation to produce T-cell immune suppression, both locally in the skin and at locations remote from the site of exposure, 11 and evidence that risk of NHL is greatly increased in people with T cell immune deficiency associated with HIV infection or treatment after organ transplantation, 12,13 make a causal association between sun exposure and NHL plausible.…”
mentioning
confidence: 99%
“…5 It is well accepted that UV-B irradiation to the skin generates the perturbation of antigen presentation with antigenspecific T-cell unresponsiveness, which results in the increased development of skin cancers 6 or decreased development of contact skin hypersensitivity. 7 Denfeld et al 8 have shown that UV-B-irradiated murine BMderived DCs suppressed proliferation of naive and primed T cells and induced antigen-specific clonal anergy in primed Th1 cells but not in naive T cells. UV-B-irradiated murine BM-derived DCs were shown to render naive T cells partially unresponsive to alloantigen.…”
Section: Introductionmentioning
confidence: 99%